A study on bioremediation of azo dyes in microbial fuel cell and its feasibility for simultaneous electricity generation - Shahi, Amrita (IIT(BHU) Varanasi, 2021)
Abstract is available in content.
Keywords: bioremediation; microbial fuel; electricity generation